Real‐life effectiveness of once‐daily calcipotriol and betamethasone dipropionate gel vs. ointment formulations in psoriasis vulgaris: final analysis of the 52‐week PRO‐long study. (3rd September 2015) - Lambert, J.; Hol, C.W.; Vink, J.
Abstract: Background: Topical therapies are the mainstay of treatment for psoriasis vulgaris. The fixed combination of calcipotriol (Cal) 50  μ g/g plus betamethasone 0.5 mg/g (as dipropionate; BD) is a first‐line topical treatment and available as a gel or ointment. The use of these fixed combination products was compared in PRO‐long, a long‐term noninterventional study, for which interim results (4 and 12 weeks) have previously been reported. Objective: To describe and compare patients' perspectives on the fixed combination gel and ointment formulations; to include efficacy, adherence behaviour, treatment satisfaction and health‐related quality of life (HRQoL) aspects during long‐term real‐life psoriasis management. Methods: PRO‐long was a multicentre, prospective, observational, 52‐week study of patients prescribed fixed combination Cal/BD gel or ointment in clinical practice. For final analysis the following were assessed at weeks 24, 36 and 52: differences in the proportion of patients with 'mild'/'very mild' disease according to patient's global assessment of disease severity, adherence behaviour, treatment satisfaction (nine‐item treatment satisfaction questionnaire for medication) and HRQoL (Skindex‐29). Results: Patients ( n  = 328) were prescribed once‐daily Cal/BD gel ( n  = 152) or ointment ( n  = 176). At week 52, a higher proportion of patients reported that the severity of their psoriasis was 'mild'/'very mild' vs. baseline (gel: 60.2 vs. 47.1%; ointment: 58.8 vs. 42.4%), with greater treatment satisfaction reported in patients using gel vs. those using ointment. A higher proportion of patients found the gel 'easy' to use compared with the ointment (66.7 vs. 45.2%). Daily application of treatment took ≤5 min for 86.1% of patients using gel and 71.0% of patients using ointment. Conclusion: This real‐life study has demonstrated similar effectiveness between the Cal/BD formulations. However, over a 52‐week treatment period, patients reported greater treatment satisfaction with the gel, which was considered easier to use, faster to apply and overall a more convenient product.